The Effect Of After-Sales Services Quality, Customer Ratings And Reviews Towards Customer Purchase Intention And Customers Loyalty Through Customers Satisfaction As Intervening Variable (Case Of Tokopedia E-Commerce Platform In Surabaya Indonesia) - MOHAMMED FATEH ALRAHMAN ALI RABBAD (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
E-commerce in indonesia is expected to keep expanding due to the high consumer spending habits of the indonesian population. Online transactions can be conducted through applications or websites accessible via smartphones, with tokopedia being one of the most prominent e-commerce platforms. The scale used in this study is the likert scale. The population in this study is tokopedia users in surabaya. Taking into account suggestion number 3 on determining the number of samples by Hair et al. (2010), total sample taken was 160. In collecting the data, the researcher distributed questionnaires by using google form to 160 users of tokopedia in surabaya city. The result of the study showed that after sales services and customer ratings and reviews had positive and significant affect toward customer purchase intention. Besides, after sales services and customer ratings and reviews had positive and significant affect toward customer loyalty. After sales services and customer ratings and reviews had positive and significant affect toward customer satisfaction. After sales services and customer ratings and reviews has a significant indirect effect on customer purchase intention through customer satisfaction. After sales services and and customer ratings and reviews has a significant indirect effect on customer loyalty through customer satisfaction.